Judgment at Nuremberg [videorecording (DVD)] - Mann, Abby; Tracy, Spencer, 1900-1967; Lancaster, Burt, 1913-1994; Dietrich, Marlene; Schell, Maximilian; Garland, Judy; Clift, Montgomery; Shatner, William; Klemperer, Werner; Christine, Virginia, 1920-1996; Laszlo, Ernest; Gold, Ernest, 1921-1999; et al. (KL studio classics., 2015)
American judge Daniel Haywood presides over the trial of four German jurists accused of "legalizing" Nazi atrocities. But as graphic accounts of sterilization and murder unfold in the courtroom, mounting political pressure for leniency forces Haywood into making the most harrowing and difficult decision of his career.